2007
DOI: 10.1080/00222930701504797
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distributions and host associations of larval parasitoids of frugivorous Drosophilidae in Japan

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 15 publications
3
143
0
Order By: Relevance
“…Populations of A. japonica on the main islands of Japan exhibit highly femalebiased sex ratios (92.7-99.2% females), whereas population sex ratios on the smaller southern islands are not biased (Mitsui et al, 2007). The populations on the main islands are infected with parthenogenesis-inducing Wolbachia, while the populations on the smaller southern islands are not (Kremer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Populations of A. japonica on the main islands of Japan exhibit highly femalebiased sex ratios (92.7-99.2% females), whereas population sex ratios on the smaller southern islands are not biased (Mitsui et al, 2007). The populations on the main islands are infected with parthenogenesis-inducing Wolbachia, while the populations on the smaller southern islands are not (Kremer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The strains were kindly provided by M.T. Kimura from cultures derived from field samples, collected along the entire length of Japan, described in Mitsui et al (2007) and Murata et al (2009). Maps of the sampled locations can be found in both papers.…”
Section: A Japonica Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological system Asobara japonica (Hymenoptera:Braconidae:Alysiinae) is a solitary endoparasitoid laying its eggs into the first or second instar larvae of Diptera and especially Drosophila species (Mitsui et al, 2007;Ideo et al, 2008). Wasps were trapped in the field using banana and natural fruits found in some localities (see Mitsui et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…A. rufescens is partially infected by a strain closely related to the CI-inducing strain wAtab1 (Dedeine et al, 2005). In a recent survey of larval parasitoids of frugivorous Drosophilidae in Japan, Mitsui et al (2007) established the geographical distribution of A. japonica. They showed that field sex ratios are typical of arrhenotokous reproduction in three populations on subtropical islands, whereas those of all five populations sampled on the main (northern) islands are highly female biased.…”
Section: Introductionmentioning
confidence: 99%